The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11096-020-01068-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potential drug–drug interactions in outpatients of a general hospital in China: a retrospective investigation

Abstract: Background Potential drug-drug interactions are important factors resulting in adverse drug reactions or therapeutic failure. Therefore, potential drug-drug interactions need to be identified to prevent the related risk and improve drug safety. Objective This study was designed to determine the prevalence of potential drug-drug interactions and investigate the association of potential drug-drug interactions with characteristics in outpatient prescriptions. Setting A large-scale general university hospital in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…The interactions between two or more drugs may exist antagonistic or synergistic effect, both of which lead to drug toxicity or undesired therapeutic effect with harmful outcomes to patients ( 3 5 ). The potential drug-drug interactions (PDDIs) were identified in around 30% of the prescriptions in the outpatient ( 6 ) and oncology departments in China ( 6 , 7 ). Even though the prevalence data is largely lacking in China, the PDDIs may be more prevalent in intensive care settings ( 8 ) and hematology ( 9 , 10 ), based on the data from other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between two or more drugs may exist antagonistic or synergistic effect, both of which lead to drug toxicity or undesired therapeutic effect with harmful outcomes to patients ( 3 5 ). The potential drug-drug interactions (PDDIs) were identified in around 30% of the prescriptions in the outpatient ( 6 ) and oncology departments in China ( 6 , 7 ). Even though the prevalence data is largely lacking in China, the PDDIs may be more prevalent in intensive care settings ( 8 ) and hematology ( 9 , 10 ), based on the data from other countries.…”
Section: Introductionmentioning
confidence: 99%
“…A study assessing outpatients in Taiwan over a period of 3 months reported prevalence of pDDIs as high as 25.6% ( Lin et al, 2011 ). A recent analysis of prescriptions issued to outpatients of a general hospital in China revealed that as many as 30.29% of them contained pDDI with C, D or X risk rating (of which category C stands for ‘monitor therapy,’ D – ‘consider therapy modification,’ and X – ‘avoid combination,’ respectively) ( Ren et al, 2020 ). Finally, among prescriptions filled at a university health center pharmacy in Jamaica, prevalence of pDDIs was 49.8% (of which 4.7% were classified as major, 80.8% as moderate and 14.5% as minor pDDIs) ( Kennedy-Dixon et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In China, researchers observed 30% of potential drug interactions in 2019, in 16,120 outpatient prescriptions, using Lexicomp UpToDate database and Stockley's drug interaction checker. 11 A national database analysis of prescribed drugs in Slovenia in 2015 identified 42% of potential drug interactions in almost 1,2 million outpatients, and estimated that 9% of the country's population was exposed to clinically relevant potential drug interactions using Lexicomp UpToDate database. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Drug-drug interaction investigations – regardless of the country or region – are mainly focused on hospitalized patients, with serious illnesses, older age, and under chronic therapeutic regimens. 10 , 11 Representativeness is also limited by restriction to a single health setting or reduced number of participants, being concentrated on drugs prescribed by physicians – thus excluding self-medication, for example – or for institutionalized individuals. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation